Effect of nicotine on serotonin (5-HT) levels in brain of depressed rats - Bhalsinge, Rahul R.; Barde, Anita A.; Worlikar, Pratibha S.; Limaye, Manasi V.; Dhole, Mrunal P.; Tilak, Abhijeet V. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Reduction in brain serotonin (5-HT) levels contributes to depression. Nicotine may have antidepressant properties and smokers self-medicate underlying depression. Epidemiological findings suggest that smokers more often demonstrate depressive symptoms than non-smokers and depressed patients are less likely to cease smoking. Therefore, the study was planned to evaluate the effect of nicotine on serotonin levels in brain of depressed rats. Methods: Antidepressant action of study drugs was evaluated using isolation induced hyperactivity model in rats. Rats were divided into five groups with six rats in each group. Study groups: Vehicle in normal rats 1 ml/kg (subcutaneous); vehicle after isolation 1ml/kg (subcutaneous); imipramine 10 mg/kg (intraperitoneal) for 7 consecutive days; single dose of nicotine 0.4 mg/kg (subcutaneous); single dose of nicotine 0.2 mg/kg (inhalational). Brain serotonin assay was carried out. The statistical significance was determined by ANOVA followed by Tukey test (p<0.05). Results: Serotonin levels (55.93ng/g of brain tissue) in rats after isolation were significantly less than in normal rats (335.87ng/g) (p<0.001). In imipramine treated group, serotonin levels (301.4ng/g) after isolation were highly significant as compared to serotonin levels in vehicle treated group after isolation (p<0.001). Nicotine administered by subcutaneous and inhalational route showed significantly higher brain serotonin levels, i.e. 175ng/g and 254.62ng/g respectively as compared to vehicle treated rats after isolation (p<0.001). Conclusions: Single dose nicotine (inhalational) produced significant antidepressant action comparable to that of seven days’ treatment of standard antidepressant drug imipramine in rats. In rats, nicotine by both routes i.e. subcutaneous and inhalational increased serotonergic activity.